Devolution of power in healthcare: A Comparative Analysis of Tamil Nadu And Sri Lanka's Northern Province - Shivani, V.; Sai Janani, G. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
How does the process of devolving power in healthcare governance influence maternal and child health outcomes in Tamil Nadu, India, and the Northern Province of Sri Lanka given their distinctive governance frameworks and socio-political contexts? This paper analyses the impact of devolution of power in healthcare on maternal and child health (MCH) by comparing Tamil Nadu, India, and the Northern Province of Sri Lanka. Two of them have been selected as they contrast the experiences of decentralized governance, and they are relevant to address health disparities. Tamil Nadu is a forerunner in the MCH outcomes within India, a federal structure which gives states autonomy of healthcare policy. Taking the autonomy, Tamil Nadu has developed strong maternal and child health systems, with support from community participation through Panchayati Raj Institutions. On the contrary the Northern Province of Sri Lanka is a rather exclusive case of post-conflict governance in a unitary system. The constraints like central intervention, fiscal restraint, and post-war infrastructural deficits are imposed over the region, while still being subject to devolutions of powers under the 13th Amendment to the Constitution and therefore impacting MCH outcomes. Due to these contrasting cases, the study of Tamil Nadu and Northern Sri Lanka could offer significant insights into governance structures that impact MCH services in multi-cultural, as well as post-conflict settings. Using a deductive qualitative research approach, this study shows that decentralization in Tamil Nadu actually promotes efficiency and equity in health care, resulting in lower maternal and infant mortality and stronger primary health care systems. In contrast, the Northern Province is plagued by mobilization of resources and governance inefficiencies, among others, and is further aggravated by post-conflict recovery challenges. The findings highlight the importance of strengthening institutional capacity, introducing fiscal decentralisation and promotion of social participation towards mother and child welfare, this study holds important suggestions for policies about healthcare system decentralization intended to counterbalance disparity in health outputs of women and children.
Keywords: Post-conflict settings; fiscal decentralization; Devolution of power; Healthcare governance; Maternal and child health